Comparison of ALK detection by FISH, IHC and NGS to predict benefit from crizotinib in advanced non-small-cell lung cancer. (May 2019) - Lin, Chen; Shi, Xun; Yang, Shao; Zhao, Jun; He, Qiong; Jin, Ying; Yu, Xinmin
Highlights: IHC had the highest positive rate, while FISH presented a certain false-negative rate. NGS positive may predict clinical benefit of Crizotinib more accurately. NGS allows efficient test for specific variants and concurrent genomic alterations. Abstract: Purpose: Anaplastic lymphoma kinase (ALK) is now a validated kinase target in non-small cell lung cancer (NSCLC). We implemented three ALK laboratory methodologies: fluorescence in situ hybridization (FISH), immunohistochemistry (IHC) and next-generation sequencing (NGS) to detect EML4-ALK fusions and compared the predictive value for Crizotinib efficacy in ALK-positive patients. Methods: 55 ALK positive patients confirmed by at least one method were enrolled in the present study, of whom 45 cases were assessed by FISH, IHC and NGS concurrently, and another 10 cases only received IHC and NGS assessment for ALK status. Results: IHC presented the uppermost positive rate (94.5%), followed by NGS (92.7%) and FISH(82.4%), among which IHC and NGS had the highest concordance rate of 87.3%. No difference was detected in ORR, DCR and PFS of ALK positive cases defined in three groups. Notably, NGS positive patients were correlated with a higher DCR and longer PFS compared to NGS negative cases (P = 0.02 and P = 0.09), while FISH and IHC status were not distinguishing in predicting the outcome of Crizotinib. TP53 concurrent mutation might reduce responsiveness to Crizotinib and worsen prognosis in ALK-rearranged NSCLC. Conclusion: FISH present a certain false-negative rate although considered the gold standard. Ventana-D5F3 IHC is qualified as a screening tool, while NGS positive may predict clinical benefit of Crizotinib more accurately, allowing efficient test for specific variants and concurrent genomic alterations.